Comparison of the results of MIS-TLIF and open TLIF techniques in laborers - Oliveira,Daniel De Abreu (2014)
Objective: To compare clinical outcomes in laborers who have undergone open transforaminal interbody fusion (TLIF) and minimally invasive transforaminal interbody fusion (MIS TLIF). Methods: 78 patients were submitted to lumbar arthrodesis by the same two spine surgeons partners from January 2008 to December 2012. Forty-one were submitted to traditional open arthrodesis and 37 to the minimally invasive procedure. Three patients were not included because they had already retired from work. The analyzed variables were length of hospitalization, length of follow-up, type of access (TILF or MIS TLIF), need for blood transfusion, percentage of improvement or worsening after surgery, pre- and postoperative VAS scale, time off work, pre-and postoperative Oswestry disability index, and general aspects of the laborers such as age, education, profession, working time, amount of daily weight carried at work, and use or not of personal protective equipment. Results: Time off work was longer in the TLIF group (average of 9.84 months) compared with the MIS TLIF group (average of 3.20 months). Significant improvement in postoperative VAS and Oswestry was achieved in both groups. Average length of hospitalization was 5.73 days for the TLIF group and 2.76 days for the MIS TLIF group. Conclusions: Minimally invasive transforaminal lumbar interbody fusion presents similar results when compared to open TLIF, but has the benefits of less postoperative morbidity, shorter hospitalization times, and faster rehabilitation in laborer patients.